2014
DOI: 10.1073/pnas.1322494111
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast remodeling during state transitions in Chlamydomonas reinhardtii as revealed by noninvasive techniques in vivo

Abstract: Plants respond to changes in light quality by regulating the absorption capacity of their photosystems. These short-term adaptations use redox-controlled, reversible phosphorylation of the lightharvesting complexes (LHCIIs) to regulate the relative absorption cross-section of the two photosystems (PSs), commonly referred to as state transitions. It is acknowledged that state transitions induce substantial reorganizations of the PSs. However, their consequences on the chloroplast structure are more controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
90
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 42 publications
11
90
1
1
Order By: Relevance
“…In general, these results, in line with similar observations [29,39,[41][42][43], underline the remarkable flexibility of the thylakoid membrane ultrastructure, which should thus not be portrayed as simply providing a scaffold for the photosynthetic functions but also actively participating in the energy conversion steps and in different regulatory functions.…”
Section: Resultssupporting
confidence: 82%
“…In general, these results, in line with similar observations [29,39,[41][42][43], underline the remarkable flexibility of the thylakoid membrane ultrastructure, which should thus not be portrayed as simply providing a scaffold for the photosynthetic functions but also actively participating in the energy conversion steps and in different regulatory functions.…”
Section: Resultssupporting
confidence: 82%
“…Recently, the process of state transitions was revisited in C. reinhardtii (Nagy et al, 2014;Ünlü et al, 2014). Interestingly, these new data indicated that although 70% to 80% of LHCII detached from PSII in state 2 conditions, only a fraction of about 20% was attached to PSI.…”
Section: Absence Of Stt7 Function Causes High Light-induced Photoinhimentioning
confidence: 99%
“…The proportion of mobile LHCII antenna is about 80% in the alga, whereas in Arabidopsis, only 15% to 20% of LHCII is transferred to PSI under state 2 conditions . However, the large increase in PSI antenna size in C. reinhardtii has recently been challenged (Nagy et al, 2014;Ünlü et al, 2014): while 70% to 80% of mobile LHCII detached from PSII in response to transition to state 2 conditions, only a fraction of about 20% functionally attached to PSI.…”
mentioning
confidence: 99%
“…Because state 2 facilitates induction of PSII activity in the absence of hydrogenase , we propose that the increase of PSI antenna size upon state 2 might enhance PSI-CEF rate (Cardol et al, 2009;Alric, 2010Alric, , 2014 and therefore promote ATP synthesis and CBB cycle activity. Nevertheless, the attachment of LHCII to PSI in state 2 has been recently called into question (Nagy et al, 2014;Ünlü et al, 2014). In this .…”
Section: Transitory Induction Of Pgrl1-dependent Psi-cef Upon Illuminmentioning
confidence: 99%